Experimental Research on Waste Fiber Recycled Concrete Beam-to-Column Joints under Monotonic Loading. (12th March 2022) - Zhou, Jinghai; Jin, Liwei; Qu, Jingtong; Sun, Hong; Kang, Tianbei; Yuan, Ye; Liu, Yu
Abstract : The mechanical properties, failure forms, and deformation characteristics of 10 beam-to-column joints under monotonic loads were compared and analyzed. The design variables were waste fiber content (0.08%, 0.12%, and 0.16%), waste fiber length (12 mm, 19 mm, and 30 mm), and replacement rate of recycled aggregates (0%, 50%, and 100%). The results indicated that, under an axial compression ratio of 0.4, all specimens underwent plastic hinge failure at the beam end under monotonic loading and experienced four stages of the initial cracking, full-cracking, limit, and failure stages. There was no shear oblique crack in the core area of the joint, and no shear failure occurred. When the replacement of recycled aggregates is 50%, the tensile strength of concrete mixed with a specific amount of fibers can be effectively improved. The ultimate bearing capacity of the beam end is improved when the length and volume of the waste fibers are 19 mm and 0.12%, respectively. The ratios between the calculated and tested ultimate bearing capacity of beam-column joints are in the 0.99–1.10 range, and the calculated and tested values are in good agreement.